PARTICIPATION BANKING AND ITS CONTRIBUTIONS TO THE TURKISH ECONOMY - Ali ESRE; Ayhan KAPUSUZOGLU; Nildag Basak CEYLAN (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2022)
In this study, participation banking, which focuses on providing banking services in accordance with religious rules and its contributions to Turkey's economy, are investigated. Participation banking is discussed in general, and the methods of using funds in participation banking are also evaluated. In addition, its differences are compared with conventional banks. With the development of participation banking in Turkey, it can be stated that the place of participation banking in the financial system is different from other banks. The distribution and number of branches of participation banks in Turkey, which continue to serve in the finance sector together with the conventional bank branches and continue their operation by trading, and operate with a different structure in the banking sector, are evaluated together with the role of the employees in participation banking. In the study, general problems of participation banking are evaluated by considering strengths and weaknesses and suggestions are made to solve the problems. Moreover, the contributions of participation banking to the Turkish economy are analyzed.